Three-dimensional visualization of movement qualities in contemporary dance - dos Anjos, K. R.; Ribeiro, C.; Fernandes, C. (Proceedings of the 5th International Conference on Movement and Computing, 2018)
Analyzing and documenting contemporary dance movement data has proven to be a very difficult task due to the vast existence of styles and aesthetics which are characteristic of each individual choreographer. Indeed, identifying movement qualities with the intention of co-relating them to specific meanings and choreographic intentions is practically impossible without taking an artist-driven approach. Moreover, equipping dancers with wearable technology in order to accurately track each of their movements is only applicable in controlled laboratory scenarios, therefore not being a viable approach to analyze large scale real-world rehearsals or performances. This paper describes a visualization system that exposes movement qualities for dance through rendering effects. Combining optical flow analysis with depth video information, we were able to estimate the three-dimensional flow for each point in the cloud. This information was used to color point cloud videos with this information, showing potential to be used for the creation of different rendering effects, which are also discussed in this paper. The data used was captured in a non-intrusive manner during the creation process of a dance piece by Portuguese choreographer Rui Lopes Graça, enabling us to examine nuances and details of the rehearsals' process, which would not be replicable in a laboratory environment.